2014
DOI: 10.1093/nar/gkt1352
|View full text |Cite
|
Sign up to set email alerts
|

The functions of DNA methylation by CcrM in Caulobacter crescentus: a global approach

Abstract: DNA methylation is involved in a diversity of processes in bacteria, including maintenance of genome integrity and regulation of gene expression. Here, using Caulobacter crescentus as a model, we exploit genome-wide experimental methods to uncover the functions of CcrM, a DNA methyltransferase conserved in most Alphaproteobacteria. Using single molecule sequencing, we provide evidence that most CcrM target motifs (GANTC) switch from a fully methylated to a hemi-methylated state when they are replicated, and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(150 citation statements)
references
References 85 publications
12
138
0
Order By: Relevance
“…4B and D). This observation is consistent with the described role of CcrMmediated methylation in mediating cell cycle progression, DNA metabolism, and cell division in C. crescentus (57,58).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…4B and D). This observation is consistent with the described role of CcrMmediated methylation in mediating cell cycle progression, DNA metabolism, and cell division in C. crescentus (57,58).…”
Section: Resultssupporting
confidence: 92%
“…In C. crescentus, the methylation of DNA by CcrM plays an important role in the regulation of cell cycle progression (57)(58)(59), and methylated sites are subject to transcriptional regulation by GcrA (14). Methylation by CcrM is conserved in other Alphaproteobacteria, including B. abortus (18), A. tumefaciens (9), and S. meliloti (60).…”
Section: Resultsmentioning
confidence: 99%
“…The cell cycle-regulating methyltransferase CcrM can modify the adenine residue in the GANTC sequence and is widespread among members of Alphaproteobacteria. It has been demonstrated that the CcrM protein is essential for the viability of S. meliloti, A. tumefaciens, Brucella abortus, and Caulobacter crescentus in rich medium cultures (49,50) and that it participates in the regulation of the bacterial cell cycle (51,52).…”
Section: Resultsmentioning
confidence: 99%
“…None of the GANTC sequences were found within the predicted "lysogeny" control region (see above). Analysis of the frequency and distribution of GANTC motifs in the available genomes of Alphaproteobacteria showed a distribution bias of GANTC motifs between the protein-coding and intergenic sequences, being on average Ͼ1.5-fold overrepresented in the intergenic regions and slightly underrepresented in the coding regions (52). It was also shown that the expression levels of 546 genes of C. crescentus were significantly altered in the strain with constitutive overexpression of CcrM compared to the wild-type strain, with 214 of these genes being affected Ͼ2-fold (52).…”
Section: Fig 4 Comparison Of Restriction Patterns Of Dammentioning
confidence: 99%
“…It is worth mentioning that, during the swarmer-cell-to-stalked-cell transition, DnaA accumulation (accompanied by CtrA degradation) leads to activation of gcrA tran- scription and subsequent CtrA expression induced by the GcrA cell cycle regulator (98). Interestingly, though there are also CcrM methylation sites within the C. crescentus origin, it seems that methylation of the origin does not play a role in regulating the initiation of chromosomal replication as it does with Dam methylase (99,100).…”
Section: Master Regulators Inhibit Replication Initiation During Thementioning
confidence: 99%